Luminescence and Light Yield of La2O3 and Gd2O3 Glass Host Co-Doped Ce3+, Pr3+ - Jitsoonthonchaiyakul, Sunisa; Pramchu, Sittichain; Chewpraditkul, Weerapong; Chen, Danping; Lertloypanyachai, Prapon (Burapha Science Journal, 2024)
Background and Objectives :Develop the efficiency of SBAL and SBALG scintillators and improve the light yield of scintillator by doping Ce3+and Pr3+ compared with BGO crystal as standard. Methodology : In this research, 2 formulas of glass scintillators were developed include: 5SiO2 - 30B2O3 - 25Al2O3 – 30La2O3 (SBAL) and 15SiO2 - 30B2O3 - 25Al2O3 – 22.5La2O3 – 7.5Gd2O3 (SBALG), Both formular were doped with Ce3+and Pr3+. The glass samples were prepared by melt-quenching method under a CO reducing atmosphere and were annealed at 700oC for 3 hours. Main Results : The absorption band of energy compose Gd3+ (4f-4f) at 272 nm, Pr3+ (4f-4f) at 400-500 nm and the absorption edge of Ce3+ (5d-4f) at 370 nm. Moreover, this research applied density functional theory (DFT) and random phase approximation (RPA) to predict the energy absorption performance of glass structures that affect the luminescence of glass samples. The emission band of the Ce3+: 5d - 4f transition region 370 - 630 nm and the emission spectra of Pr3+ (4f-4f) of glass samples SBAL and SBALG at the energy level 1D2 ®3H4 transition at 604 nm. Conclusions : Excitation glass sample with X-rays irradiation found that the luminescence efficiency was about 2.52% of SBAL and 7.83% of SBALG glass sample compared with BGO crystals. The light yield (LY) tested under excitation with a particles (238Pu) found that the SBALG glass sample has enegy value higher than SBAL compared with BGO crystal. So SBALG glass structure is suitable for using scintillator material because of it has the good ability to react with radiation.